2021
DOI: 10.1155/2021/9920364
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Regulation of Microglia Gene Expression by Natural Molecules in Herbal Medicine

Abstract: The activated microglia contribute to stroke-induced neuroinflammation by upregulating the expression of a pleura of genes that are characterized as either proinflammatory or anti-inflammatory. The natural products alantolactone (Ala) and dehydrodiisoeugenol (Deh) found in Inula helenium L. and Myristica fragrans Houtt., respectively, are regularly used in traditional herb medicine, which play anti-inflammatory and antioxidant roles via regulation of canonical pathways such as nuclear factor kappa B (NF-κB) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…It has been confirmed that EW improves neurobehaviors in rodents with middle artery occlusion-reperfusion injury and has specific preventive and therapeutic effects in treating stroke [15][16][17]. EW can also markedly decrease the cytokine expressions for inflammation, such as TNF-α, IL-6, and IL-1β in the brain, decrease apoptosis, and improve nervous system symptoms related to inflammation [15,18,19]. The EW basic formulation consists of 10 drugs for the treatment of nervous system diseases, selected from EW formulation based on Mongolian medical theory.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been confirmed that EW improves neurobehaviors in rodents with middle artery occlusion-reperfusion injury and has specific preventive and therapeutic effects in treating stroke [15][16][17]. EW can also markedly decrease the cytokine expressions for inflammation, such as TNF-α, IL-6, and IL-1β in the brain, decrease apoptosis, and improve nervous system symptoms related to inflammation [15,18,19]. The EW basic formulation consists of 10 drugs for the treatment of nervous system diseases, selected from EW formulation based on Mongolian medical theory.…”
Section: Introductionmentioning
confidence: 87%
“…Currently, the administration of EW in the therapeutic application of neuronal dysfunction is attracting increasing attention and many related studies have been conducted in China. It has been confirmed that EW improves neurobehaviors in rodents with middle artery occlusion-reperfusion injury and has specific preventive and therapeutic effects in treating stroke [15][16][17]. EW can also markedly decrease the cytokine expressions for inflammation, such as TNF-α, IL-6, and IL-1β in the brain, decrease apoptosis, and improve nervous system symptoms related to inflammation [15,18,19].…”
Section: Introductionmentioning
confidence: 92%
“…Luteolin is a flavonoid compound that protects mouse neurons and alleviates depressionlike behavior in CUMS mice via the Sirt1/NF-κB/NLRP3 signaling Frontiers in Pharmacology frontiersin.org pathway (Xie et al, 2023). Dehydrodiisoeugenol, which play antiinflammatory and antioxidant roles via regulation of canonical pathways such as nuclear factor kappa B (NF-κB) in microglia and microphages (Qiburi et al, 2021). Regeneration of nerves is a complex process involving multiple pathways.…”
Section: Effect Of Ecs On Nf-κb Signaling In the Hippocampi Of Mice W...mentioning
confidence: 99%
“…It has been con rmed that EW improves neurobehaviors in rodents with middle artery occlusion-reperfusion injury and has speci c preventive and therapeutic effects in treating stroke [5]. EW can also markedly decrease the cytokine expressions for in ammation, such as TNF-α, IL-6 and IL-1β in the brain, decrease apoptosis, and improve nervous system symptoms related to in ammation [5][6][7]. The EW basic formulation consist of 10 drugs for the treatment of nervous system diseases, selected from EW formulation based on Mongolian medical theory.…”
Section: Introductionmentioning
confidence: 99%